KEBIJAKAN GAMBIA KELUAR DARI MAHKAMAH INTERNASIONAL PADA ERA PEMNTAHAN YAHYA JAMMEH - Fiki Irianto Kayupa; Sri Muryantini (Jurnal Studi Diplomasi dan Keamanan, 2018)
This study aims at discussingwhat factors behind the Gambian policy to leave the International Criminal Court. Moreover, it will explain what forms of discrimination carried out by the International Criminal Court as well as Yahya Jammeh's policies that have become controversial and criticized by the Gambia people and the international community.Gambia withdrawalfrom the International Criminal Court in Yahya Jammeh's Era. The International Criminal Court is a permanent international court established to investigate, prosecute and try individuals accused of committing the most serious crimes of concern to the international community as a whole, namely the crime of genocide, crimes against humanity, war crimes and the crime of aggression.To date,  almost all of its full-fledged investigations have focused on Africa. Gambia demanded the International Criminal Court to prosecute the European Union for the death of African migrants on the European Coast and sued former British Prime Minister Tony Blair for his suspicion in the Iraq War. In addition, the double standards imposed by the International Criminal Court against the UN Security Council led to criticism from African countries, especially the Gambia. The case of Sudan (Darfur) and Libya are referred to by the UN Security Council while 3 of the 5 veto holders are not members of the International Criminal Court. On the other hand, the Yahya Jammeh Government has come under fire from the international and national Gambia for the violence committed against the people, especially against the opposition members, human right defenders, journalists and the LGBT communties. The European Union, the United Nations, Amnesty International and Human Rights Watch, demand the International Criminal Court to investigate Yahya Jammeh's Government.